2004
DOI: 10.1177/101053950401600203
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Low Birth Weight and its Determinants in an Urban Resettlement Area of Delhi

Abstract: Birth weight remains an important factor affecting infant and child mortality. Many factors influence the occurrence of low birth weight (LBW). The present study was conducted to study the prevalence and determinants of LBW in an urban resettlement area of Delhi. A baseline survey was done to enroll all pregnant women in the area. These women were followed up every month till outcome. The prevalence of LBW was 39.1%. Occurrence of LBW was related to age, parity, weight and height of the mother. In multiple log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
22
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 6 publications
10
22
2
1
Order By: Relevance
“…Our findings are consistent with the studies done by Chhabral et al and Khatun et al 31,32 In our study significant correlation was noted between the parity and birth weight. Our findings were consistent with Chhabral et al, Khatun et al 31,32 In the present study a significant association was found between socioeconomic status and birth weight of baby.…”
supporting
confidence: 83%
“…Our findings are consistent with the studies done by Chhabral et al and Khatun et al 31,32 In our study significant correlation was noted between the parity and birth weight. Our findings were consistent with Chhabral et al, Khatun et al 31,32 In the present study a significant association was found between socioeconomic status and birth weight of baby.…”
supporting
confidence: 83%
“…20 In this study almost half (41.5%) of the babies were less than 2.5kg whereas a lesser proportion of newborns were having low birth weight in a study conducted by Paul et al (28.3%) Chabbra (39.1%) and Chowdary (36.2%). [21][22][23] In the present study, 14.7% of children less than two years were found to be partially immunized or not immunized at all. Whereas a greater proportion of children were not immunized in a study conducted by Pahwa et al (56.7%) and Singhal et al (44.99%).…”
supporting
confidence: 44%
“…This incidence of VLBW is higher in women weighing less than 40 kg when compared to women weighing more than 40 kg. These observations are in accordance with the results of Chhabra et al 10 Mid-arm-circumference of the mother was cent percent related to incidence of VLBW. Mid-arm-circumference tells the real status of maternal nutrition.…”
Section: Discussionsupporting
confidence: 82%